Comparative performance analysis of SDN vs traditional networks using SDN controller - Shahriar, Md. Sakib; Sabit, Jahid Hossain; Ahmed, Akib; Amiruzzaman (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.